The dynamics of space use in some Lake Malawi fishes - Robinson, Rosanna Lesley (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1996)
Behaviour and space utilisation of rock-dwelling cichlids were observed at Thumbi East Island, Lake Malawi. 1. Males of five species of the mbuna complex held long-term territories. Pseudotropheus elongatus "aggressive" vigorously defended a feeding area and sometimes a spawning site interspecifically, but did not feed in the peripheral part of their territory. Spawning sites of Pseudotropheus zebra, Pseudotropheus tropheops "orange chest", Labeotropheus fuelleborni, and Petrotilapia nigra were interspecifically-defended, while larger mating territories were defended against conspecific neighbours. Feeding areas were shared with many fish and often extended beyond the defended area. There was considerable variation in behaviour and space use within and between species and between times of day. 2. Non-territorial P. zebra used larger ranges than territorial conspecifics, and fed more on plankton, but individuals had preferred benthic feeding areas, often in conspecific territories. These 'floaters' were often aggressive. Both size and relative brightness independently predicted the outcome of aggressive interactions between floaters, and a site-specific dominance hierarchy was suggested, with some individuals appearing to be semi-territorial. 3. Males and females of 21 and 13 species respectively were found to establish temporary breeding territories. Overall breeding seasonality was bimodal, but reproductive timing and territory characteristics differed among species. Temporary territories had a considerable impact on the behaviour and habitat use of all resident mbuna species, even causing abandonment of territories. 4. Non-breeding Protomelas taeniolatus had limited home ranges, and showed little aggression. During the highly-synchronised reproductive season, males defended spawning sites and females fry-guarding territories. Most chases were directed towards the commonest fish, but predators were chased further and faster. Female behaviour changed over the guarding period. Females generally continued territorial defence after the brood had disappeared. Most broods contained fry of different sizes and species. Significant benefits were found for guarding females with clustered territories, but females did not appear to choose sites adjacent to conspecific parental females. 5. Territoriality in fish is taxonomically widespread and may serve several functions according to species, sex and developmental stage. It also varies according to genotype- and phenotype-limited strategies and short term costs and benefits. Territories may be simultaneously multifunctional.
Keywords: Cichlids -- Nyasa, Lake; Fishes -- Malawi; Fishes -- Nyasa, Lake